Improvement of cassava: A tropical root crop - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1971)
This is an overview of the present status of cassava as regards production and yields, nutritional value and international research programs. A cassava research program to be developed by CIAT is presented. The program covers the following areas: varietal improvement, production systems, international testing, plant protection, research on utilization, agricultural engineering, agricultural economics, training and literature. A five-year budget (1972-76) is included. (CIAT)